2018
DOI: 10.1152/ajpendo.00081.2018
|View full text |Cite
|
Sign up to set email alerts
|

Propionate-induced changes in cardiac metabolism, notably CoA trapping, are not altered byl-carnitine

Abstract: High concentrations of propionate and its metabolites are found in several diseases that are often associated with the development of cardiac dysfunction, such as obesity, diabetes, propionic acidemia, and methylmalonic acidemia. In the present work, we employed a stable isotope-based metabolic flux approach to understand propionate-mediated perturbation of cardiac energy metabolism. Propionate led to accumulation of propionyl-CoA (increased by ~101-fold) and methylmalonyl-CoA (increased by 36-fold). This accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 47 publications
1
34
0
Order By: Relevance
“…The hearts were allowed to beat spontaneously throughout the perfusion. All heart perfusions underwent an initial 15-min equilibration period with Krebs Ringer bicarbonate buffer containing 119 mM NaCl, 4.8 mM KCl, 2.6 mM CaCl 2 , 1.2 mM KH 2 PO 4 , 1.2 mM MgSO 4 , 25 mM NaHCO 3 , 11 mM glucose, and 0.05 mM L-carnitine at a flow rate of 12 ml/min for rats or 1.5 ml/min for mice [51][52][53] . At the end of each perfusion, hearts were immediately freeze-clamped in liquid nitrogen using the Wollenberger technique and stored at −80°C for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The hearts were allowed to beat spontaneously throughout the perfusion. All heart perfusions underwent an initial 15-min equilibration period with Krebs Ringer bicarbonate buffer containing 119 mM NaCl, 4.8 mM KCl, 2.6 mM CaCl 2 , 1.2 mM KH 2 PO 4 , 1.2 mM MgSO 4 , 25 mM NaHCO 3 , 11 mM glucose, and 0.05 mM L-carnitine at a flow rate of 12 ml/min for rats or 1.5 ml/min for mice [51][52][53] . At the end of each perfusion, hearts were immediately freeze-clamped in liquid nitrogen using the Wollenberger technique and stored at −80°C for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The derivatized samples were centrifuged for 5 min at 20,000× g , and the supernatants were transferred to GC vials for GC-MS analysis. A modified GC-MS method was employed [ 21 ]. The injection volume was 1 μL, and samples were injected in splitless mode.…”
Section: Methodsmentioning
confidence: 99%
“…Propionate has been demonstrated to possess anti-inflammatory effects such as the alleviation of cardiac hypertrophy, fibrosis, vascular dysfunction, and hypertension through T cell-dependent regulation in an angiotensin II-infused mouse model ( 19 ). However, Wang et al reported that propionate interfered with fatty acid oxidation as a fuel resource for heart due to the lack of specific enzyme-utilizing short-chain (C3, C4) fatty acids in the propionate-perfused heart ( 20 ), suggesting that higher plasma propionate might cause adverse cardiac effects such as heart failure ( 20 ). This finding might explain the frequent association of cardiovascular dysfunction with dramatic increases in circulating concentrations of propionate or its metabolites in certain diseases, such as obesity, diabetes, and non-CAKUT renal diseases (compared with CAKUT) ( 8 10 , 21 ).…”
Section: Discussionmentioning
confidence: 99%